Cuddle Bear's book of hugs - Freedman, Claire; Scott, Gavin (Tulsa, OK : Kane Miller, a Division of EDC Publishing, 2017)
"Meet the bears of Cuddle School. The hug-you-happy crew. They're learning every type of hug to find one right for you!"--
Keywords: Teddy bears -- Juvenile fiction; Hugging -- Juvenile fiction; Bears -- Juvenile fiction; Stories in rhyme; Teddy bears -- Fiction; Hugging -- Fiction; Schools -- Fiction; Teddy bears -- Juvenile literature; Bears; Hugging; Teddy bears; Juvenile works